Study on Certain Subclass of Analytic Functions Involving Mittag-Leffler Function. (28th October 2021) - Alessa, Nazek; Venkateswarlu, B.; Loganathan, K.; Thirupathi Reddy, P.; Shashikala, A.; Namgyel, Ngawang
Abstract : We propose and explore a new subclass of regular functions described by a new derivative operator in this paper. Some coefficient estimations, growth and distortion aspects, extreme points, star-like radii, convexity, Fekete-Szego inequality, and partial sums are derived.